KONFLIK BATIN TOKOH UTAMA DALAM FILM HOPE MENGGUNAKAN PENDEKATAN PSIKOLOGI SASTRA - Sari, Ayu Intan; Mulyaningsih, Indrya; Nuryanto, Tato (Magistra Andalusia: Jurnal Ilmu Sastra, 2022)
This article aims to analyze the inner conflict of the character So Won in the 2013 film Hope based on Abraham Maslow's theory of multilevel needs.  This research uses descriptive qualitative method.  Data collection uses the technique of observing and noting. Data analysis uses the equivalent method. From the results of the analysis, it can be concluded that there are 17 inner conflicts experienced by the character So Won.  The 17 data are then grouped based on Maslow's multilevel needs theory, namely: (a) there are 3 physiological needs, (b) there are 4 data for security needs, (c) there are 3 data for belonging and love needs, (d)  there are 2 data for appreciation needs, and (e) there are 5 data for self-actualization needs.  The basic needs that are not met by the character So Won mostly occur due to circumstances and bad events that have befallen him.  This bad event causes the main character's inner conflict to arise.  So that their basic needs are not met.  This research is expected to be useful as a scientific treasure of inner conflict using a literary psychology approach.  In addition, as a reference for other authors for this type of research in the same direction.  The benefits of this research can also be taken and accepted by students, teachers, viewers, playwrights (screenplay), and other writers.